Left ventricle end‐systolic elastance, arterial‐effective elastance, and ventricle‐arterial coupling in Epilepsy. (26th August 2020) - Fialho, Guilherme L.; Wolf, Peter; Walz, Roger; Lin, Katia
Abstract : Objective: Sudden unexpected death in epilepsy (SUDEP) is a tragic event. Cardiac models of sudden death state that, paradoxically, healthy individuals compose most of the victims of this event. Exploration of cardiac physiological variables related to outcome could help unveil risk markers for sudden death in epilepsy. We investigated left ventricle end‐systolic elastance, arterial‐effective elastance and ventricle‐arterial coupling (VAC) in PWE compared with controls. Material & Methods: Adult patients with temporal lobe epilepsy without known cardiovascular diseases were submitted to treadmill test and transthoracic echocardiogram. Individuals without epilepsy matched by sex, age, and body mass index composed the control group. Cardiac risk factors, exercise performance, autonomic data from treadmill test, systolic and diastolic function, morphological cardiac data, and left ventricle pressure‐volume loop were recorded. Results: Sixty subjects were consecutively enrolled (30 PWE and 30 controls). Epilepsy duration was 22.5 ± 10.7 years (age of onset 15.2 ± 10.1 years). Treadmill variables were significantly worse in TLE patients compared with controls. End‐systolic elastance, arterial‐effective elastance, and ventricle‐arterial coupling were similar between groups. Female sex, percentage of maximal predicted heart rate achieved in exercise, exercise time, and epilepsy duration explained 28, 4% of VAC in PWE in multiple stepwise linear regression ( P = .018). Conclusions: Some aspects of the cardiac pressure‐volume curves, mainly linked to left ventricle systolic performance, contractile function and their interaction with afterload appears normal in young PWE and cannot explain their increase risk to adverse outcomes or lower physical fitness.